Semiotics Analyisis of Representation Chinese Culture in Sony Pictures Animation Film Wish Dragon Movie - Shafira, Violita; Rui, Chen (Mandarinable: Journal of Chinese Studies, 2000)
This research is entitled Representation of Chinese Culture in Wish Dragon Movie. Using semiotic analysis according to Roland Barthes. Semiotic analysis is used to analyze the signs that represent culture in the film Wish Dragon. This study aims to find the existence of a sign and then find out how Chinese culture is represented through the film Wish Dragon Movie by examining the meaning of denotation, connotation and myth according to Roland Barthes' semiotic model. In addition to finding out how the foreign audience acceptance to the Wish Dragon film and how the foreign audience understands the Chinese culture in this film, the researcher using audience comments in the most popular rated movies website to analyze.